A Study on Common Risks and Body Parts Complaints by Standing Workstation Female Operators in an Electronics Product Manufacturing Company - Deros, B.M.; Khamis, N.K.; Ghani, J.A.; Yusoff, A.R.M.; Salleh, C. (Applied Science and Engineering Progress, 2013)
Ergonomics have improved the scope on safety and minimize risk at workplace by looking into possible factors effecting product quality, work performance and machine efficiency. The main objectives of this study are to assess, identify risks and body parts that received high number of complaints with respect to standing workstation. The methodology use in this study includes anthropometric data measurements of 146 female Malaysian operators, standing risk assessment and body parts symptoms survey form. Anthropometric data measurement results in company X showed the current standing workstation match with the female operators working height and workspace. The common risks identified for standing work are awkward posture, contact stress, wrist, static posture, fatigue, twisting of the spine, bending, too far and not reachable. Three body parts (i.e. shoulder, ankle/feet and neck) received 53% of total complaints in terms of pain and un-comfortableness. Therefore, the authors strongly recommended company X top management to find the solution to this pain and un-comfortableness complaints